Inhibition of oxidative stress by testosterone improves synaptic plasticity in senescence accelerated mice. Issue 20 (18th October 2019) - Wang, Lu; Pei, Juan-Hui; Jia, Jian-Xin; Wang, Jing; Song, Wei; Fang, Xin; Cai, Zhi-Ping; Huo, Dong-Sheng; Wang, He; Yang, Zhan-Jun
ABSTRACT: It is well known that synaptic plasticity is associated with cognitive performance in Alzheimer's disease (AD). Testosterone (T) is known to exert protective effects on cognitive deficits in AD, but the underlying mechanisms of androgenic action on synaptic plasticity remain unclear. Thus, the aim of this study was to examine the protective mechanism attributed to T on synaptic plasticity in an AD senescence accelerated mouse prone 8 (SAMP8) model. The following parameters were measured: (1) number of intact pyramidal cells in hippocampal CA1 region (2) phosphorylated N-methyl-D-aspartate receptor-1 ( p -NMDAR1) and (3) phosphorylated calmodulin-dependent protein kinase II ( p -CaMKII). In addition, the content of whole brain malondialdehyde (MDA) as well as activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were determined. Treatment with T significantly elevated the number of intact pyramidal cells in hippocampal CA1 region and markedly increased hippocampal protein and mRNA expression levels of p -NMDAR1 and p -CaMK II. Further, T significantly decreased whole brain MDA levels accompanied by elevated activities of SOD and GSH-Px. Data suggest that the protective effects of T on synaptic plasticity in a mouse AD model may be associated with reduction of oxidant stress.